In vitro Selection of Resistance to Sofosbuvir in HCV Replicons of Genotype-1 to -6. Issue 7 (October 2017) - Xu, Simin; Doehle, Brian; Rajyaguru, Sonal; Han, Bin; Barauskas, Ona; Feng, Joy; Perry, Jason; Dvory-Sobol, Hadas; Svarovskaia, Evguenia S; Miller, Michael D; Mo, Hongmei
Background: Sofosbuvir is a nucleoside analogue inhibitor of the HCV NS5B polymerase approved for treatment of HCV-infected patients in combination with ribavirin or with other antivirals. It has activity against all genotypes of HCV. Resistance to sofosbuvir in genotype-1 and -2 HCV is conferred by the S282T substitution in NS5B. Methods: To begin to define the correlates of resistance to sofosbuvir in other genotypes, we performed selection experiments in cell culture using cell lines containing subgenomic replicons derived from genotypes-1b, -2a, -3a and -4a, or chimeric replicons in a genotype-1b background but encoding genotype-2b, -5a and -6a NS5B polymerase. Results: In every case, S282T was selected following passage in the presence of increasing concentrations of sofosbuvir for 10 to 15 weeks. When introduced as a site-directed mutant, S282T conferred reductions in sofosbuvir susceptibility of between 2.4 and 19.4-fold. Other substitutions observed during the selections had relatively less impact on susceptibility, such as N237S in genotype-6a (2.5-fold). Replication capacity was affected by the introduction of S282T in all genotypes to variable extents (3.2% to 22% of wild type). Conclusions: These results confirm that S282T is the primary sofosbuvir resistance-associated substitution and that replication capacity is reduced when it is present in all genotypes of HCV.